2018
DOI: 10.1016/j.jneb.2018.04.226
|View full text |Cite
|
Sign up to set email alerts
|

Food and Nutrition Literacy Research: Content Analysis

Abstract: Objective: The objective of this study was to assess the feasibility of using digital template photos to estimate children's dietary intake in childcare settings. Study Design, Setting, Participants, Intervention: Photos of preschool children's meals were taken before consumption, when any additional servings were provided, and after consumption. Weights and template photos of each meal component were taken separately, at decreasing portion sizes beginning with the serving size given during mealtime and ending… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…Mothers play a role in directing children in socializing with their surroundings. The social setting will teach children about environmental conditions, culture, language skills, and relationships (Purnomo, 2013): (Aktas et al, 2018 In the interview about the physical and social environment, there are three sub-themes, namely the way the mother in maintaining environmental health, the way the family in managing children's health, and the child's communication media. The conceptual framework by UNICEF in (Hartasari, Anggitya Titis and Muslifah Rachmawati, 2015) that affects children's health is maternal attention to children, stimulation/stimulus to children, hygiene practices, and care when a child is sick.…”
Section: Resultsmentioning
confidence: 99%
“…Mothers play a role in directing children in socializing with their surroundings. The social setting will teach children about environmental conditions, culture, language skills, and relationships (Purnomo, 2013): (Aktas et al, 2018 In the interview about the physical and social environment, there are three sub-themes, namely the way the mother in maintaining environmental health, the way the family in managing children's health, and the child's communication media. The conceptual framework by UNICEF in (Hartasari, Anggitya Titis and Muslifah Rachmawati, 2015) that affects children's health is maternal attention to children, stimulation/stimulus to children, hygiene practices, and care when a child is sick.…”
Section: Resultsmentioning
confidence: 99%
“…The results indicated that the quantity of β-glucan in cracker formulations was associated with lower HI, resulting in a decrease in the anticipated glycemic index (pGI) (Table 10). Several studies have shown that a low-GI diet improves the metabolic effects of insulin resistance and reduces insulin resistance [41]. Improvements in fibrinolytic activity may benefit the management of diabetes and cardiovascular disease, in conjunction with changes to glucose and lipid metabolism [41].…”
Section: This Table Displays Thementioning
confidence: 99%
“…Several studies have shown that a low-GI diet improves the metabolic effects of insulin resistance and reduces insulin resistance [41]. Improvements in fibrinolytic activity may benefit the management of diabetes and cardiovascular disease, in conjunction with changes to glucose and lipid metabolism [41]. Slow-digesting starch refers to a starch fraction that is digested gradually but incompletely in the large intestine, while fast-digesting starch leads to a rapid increase in blood glucose levels consumption [42].…”
Section: This Table Displays Thementioning
confidence: 99%
“…Selain itu, secara bersamasama dengan kalangan akademisi, organisasi sektor publik dan swasta harus bekerja sama untuk melakukan studi yang lebih komprehensif dan terperinci untuk menentukan persyaratan penting untuk literasi makanan dan gizi. 9 Berdasarkan latar belakang tersebut, maka penting untuk dilakukan penelitian untuk mengetahui sejauh mana tingkat literasi pada remaja dan bagaimana hubungannya dengan asupan makan dan status gizi remaja. Penelitian ini dapat menjadi suatu model untuk pengembangan pendidikan gizi yang dilakukan di tingkat sekolah.…”
Section: Pendahuluanunclassified